Dealing with the locality at the Islamic tourism destination from the Islamic perspective in Malaysia - Ruzulan, Zulaipa; Jamaludin, Mohammad Aizat; Hashim, Khairusy Syakirin Has-Yun (MDPI, 2022)
Government authority plays a significant role in ensuring the aim of being a famous Islamic tourism destination is achievable with proper planning and implementation. However, challenges to sustain Islamic tourism destination could be triggered if the government fails to manage localities where it will probably face participatory unwillingness among the society in terms of tourism development. Therefore, this paper carried out an exploratory study on the significance of considering the locality to promote an Islamic tourism destination from the Islamic perspective in Malaysia. Document analysis was chosen in this qualitative research that involves retrieving the data from the journal articles, government reports, and any reliable sources on websites. This study found that the spirit of governing tourism destinations aligns with Shariah principles as well as other sustainability motives, which leads to success where understanding the local context plays a significant role in realizing this mission.